Identifying gaps in healthcare: a qualitative study of Ukrainian refugee experiences in the German system, uncovering differences, information and support needs - Kristin Rolke; Johanna Walter; Klaus Weckbecker; Eva Münster; Judith Tillmann (BMC, 2024)
Abstract Background The 5.8 million Ukrainian refugees arriving in European countries must navigate varying healthcare systems and different and often unknown languages in their respective host countries. To date, there has been little exploration of the experiences, perceived differences, information and support needs of these refugees regarding the use of healthcare in Germany. Methods We conducted ten qualitative interviews with Ukrainian refugees living in Germany from February to May 2023, using Ukrainian, English and German language. The transcribed interviews were analysed using the qualitative content analysis method according to Kuckartz and Rädiker with the MAXQDA software. Results In general, participants consistently had a positive experience of the German healthcare system, particularly regarding the quality of treatments and insurance. Differences have been reported in the structure of the healthcare systems. The Ukrainian healthcare system is divided into private and state sectors, with no mandatory insurance and frequent out-of-pocket payments. Pathways differ and tend to focus more on clinics and private doctors. General practitioners, often working in less well-equipped offices, have only recently gained prominence due to healthcare system reforms. Initiating contact with doctors is often easier, with much shorter waiting times compared to Germany. Interviewees often found the prescription requirements for many medications in Germany to be unusual. However, the mentioned differences in healthcare result in unmet information needs among the refugees, especially related to communication, navigating the healthcare system, health insurance, waiting times and medication access. These needs were often addressed through personal internet research and informal (social media) networks because of lacking official information provided during or after their arrival. Conclusions Despite the positive experiences of Ukrainian refugees in the German healthcare system, differences in the systems and language barriers led to barriers using healthcare and information needs among refugees. The dissemination of information regarding characteristics of the German health care system is crucial for successful integration but is currently lacking. Trial Registration German Clinical Trials Register: DRKS00030942, date of registration: 29.12.2022.